Exosomes Derived From M2 Macrophages Facilitate Osteogenesis and Reduce Adipogenesis of BMSCs - Li, Ziyi; Wang, Yafei; Li, Shilun; Li, Yukun (Frontiers in Endocrinology, 2021)
Bone regeneration is a complex process which need the coordination of osteogenesis and osteoclastogenesis. The balance between osteogenesis and adipogenesis of bone marrow mesenchymal stem cells (BMSCs) plays a vital role in the process of bone formation. Recently, the intercellular communication between bone cells and surrounding cells has been gradually recognized. Moreover, macrophages on the surface of bone has been proved to regulate bone metabolism. However, the underlying mechanisms are still less known. Recent researches have indicated that exosomes are vital messenger for cell-cell communication in a various of biological processes. In this experiment, we found that exosomes derived from M2 macrophages (M2D-Exos) could inhibit adipogenesis and promote osteogenesis of BMSCs. M2D-Exos intervention increased the expression of miR-690, IRS-1 and TAZ in BMSCs. Additionally, miR-690 knock-down in M2 macrophages with miR-690 inhibitor could partially counteracted the effect of M2D-Exos on BMSCs differentiation and the up-regulation of IRS-1 and TAZ. Taken together, the results of our study indicating that exosomes isolated from the M2 macrophages could facilitate osteogenesis and reduce adipogenesis through miR-690/IRS-1/TAZ, which might as a therapeutic tool for boneloss – associated disorders.